Combining Energy and Long-term Cost Efficiency Evaluation within a Single Model. (November 2015) - Schmidt, Simon
Abstract: This paper shows a way to combine transient energy calculations and cost calculations in one tool. IDA ICE is utilized for all energy simulations and the NPV calculations are added within a Java framework. A user friendly interface allows various setups in geometry, orientation, location, construction, costs, etc. and starts all necessary calculations. The paper shows in detail the used algorithms implementing the NPV-method as well as the new simulation tool. Examples are given for evaluation and discussion of the first results.